Tricritical crossover in earthquake preparation by analyzing preseismic electromagnetic emissions. (March 2015) - Contoyiannis, Y.; Potirakis, S.M.; Eftaxias, K.; Contoyianni, L.
Highlights: Fracture-induced pre-earthquake electromagnetic emissions (EME) are studied. A crossover, tricritical, state in earthquake preparation is investigated. Analysis is performed using the method of critical fluctuations and Hurst exponent. Results reveal tricritical behavior before the final avalanche-like kHz emission. Abstract: Fracture-induced electromagnetic emissions (EME) have been observed from the laboratory to the geophysical scale permitting the monitoring of damage evolution. It has been shown that the first appearing MHz EME presents second-order phase transition characteristics and has been attributed to the fracture process of the heterogeneous medium surrounding the family of strong entities (asperities) distributed along the fault sustaining the system. The finally, abruptly, emerged strong avalanche-like kHz EME do not present any footprint of a second-order transition in equilibrium, while they have been attributed to the fracture of the family of the, relatively homogeneous, asperities themselves. In the present work we show that between these two stages of the fracture process, an intermediate stage exists. This is reflected to the tricritical behavior which is revealed for the kHz EME just before the emergence of the strong avalanche-like kHz emission. The identification of this tricritical behavior is performed using the method of critical fluctuations (MCF). The results obtained for the kHz time-series are compatible with the results obtained for an introduced model map which describes the tricritical crossover. A Hurst exponent analysis shows that this crossover indicates the limit of an antipersistence dynamics. It is finally shown, by the MCF, that first-order phase transition characterizes the final rupture of the asperities.